Evaluation of functional microbes in explaining biofilter performance during start-up1. (20th December 2020) - Zhang, Shiyang; Xia, Shibin; Sang, Wenjiao; Yuan, Julin; Guo, Weijie
Abstract: As an effective alternative for dissolved nitrogen removal, biofilter normally associates its treatment performance to various microbial communities that are shaped by different structural/operational conditions. In this study, a set of four different biofilters including MAVF (mature aerated vertical flow), NAVF (new aerated vertical flow), NVF (new non-aerated vertical flow) and BHF (baffled non-aerated horizontal flow) were employed to treat simulated domestic wastewater and the potential relationships between purification performance and functional microbes during start-up were explored. It was found that the four filters could be well clustered or separated according to their performance with the MAVF having the highest nitrogen removal, i.e. 52% for total nitrogen (TN) and 85% for total inorganic nitrogen (TIN). Moreover, TIN should be mainly removed by simultaneous nitrification-endogenous denitrification in aerobic/facultative systems. Microbial community analysis revealed that the entire and the first 20 dominant taxa, nitrifiers, and methanotrophs all displayed a similar clustering pattern, which was consistent with that of treatment performance indicating the defined purification was not only determined by functional microbes but also related to the entire microbial community. Nevertheless, Planctomycetes, Candidatus Saccharibacteria, and Candidatus Accumulibacter all displayed a weak association with performance implying these functional microbes contributed little to performance. This was probably attributed to the low inflow load as well as the lack of alternate anaerobic/aerobic conditions inside the filter bed. These findings might be helpful for biofilter optimization or management. Graphical abstract: Image 1 Highlights: Structural/operational distinction of biofilter led to great differences in performance. Both the entire and dominant microbial taxa related to treatment performance. Ammonia-oxidizing archaea/bacteria and nitrite-oxidizing bacteria all contributed to nitrification. Planctomycetes, Candidatus Saccharibacteria, and Candidatus Accumulibacte r contributed little to performance. Methanotrophs other than methanogens closely associated with treatment performance.